GROWTH, FLOWERING, FRUIT SETTING AND MATURITY BEHAVIOUR OF CORIANDER (CORIANDRUM SATIVUM L.) WITH ORGANICS INCLUDING BIOFERTILIZERS AND INORGANICS - V. HNAMTE; R. CHATTERJEE; C. TANIA (The Bioscan, 2013)
A field experiment was conducted during 2008-09 and 2009-10 to study the effect of different bio-fertilizers namely PSB, Nitrate fixers and KM along with Vermicompost (2 tha-1), NPK (30:30:15 kg ha-1) and organic manures (cow dung @ 20t ha-1) on growth behavior of coriander. There were 9 treatments with 3 replications. Combined inoculation of biofertilizers along with vermicompost and NPK (T6) showed superiority with respect to plant height both at 45 DAS (40.80cm) and at maturity (63.96 cm), number of primary (7.42) and secondary branches (13.07), stem girth (3.37cm), root length (14.39cm) followed by T3 treatment (Azospirillum + Vermicompost + NPK) where the plant height, number of primary and secondary branches, stem girth and root length were 63.09cm, 7.35, 12.22, 3.27cm and 14.05cm respectively. Treatment T6 also exhibited earliness for 50% flowering (61.66) and seed setting (79.49), days for fruit setting (96.79) and maturity (103.96). Seed yield was also obtained higher with T6 (13.34 tha-1) followed by T3 (13.06 tha-1), and was obtained lowest (6.19 tha-1) when plants were raised with cow dung manure. The use of bio-fertilizers is therefore recommended as an approach to integrated nutrient management for better yield in coriander and sustenance of soil health.